Early Serum Procalcitonin Level after Primary Total Hip Replacement. (13th May 2013) - Bouaicha, Samy; Blatter, Samuel; Moor, Beat K.; Spanaus, Katharina; Dora, Claudio; Werner, Clément M. L.
Abstract : Background . Procalcitonin (PCT) is a useful surrogate marker for the differentiation of postoperative infection and unspecific inflammatory reaction after surgery. It is known that postoperative course of the PCT serum level varies with type of surgery. No data exists about the postoperative course of serum PCT levels after primary total hip replacement (THR). Purpose . To characterize early postoperative serum PCT levels in uneventful primary THR compared to postoperative levels of different frequently used inflammatory blood parameters. Method . We prospectively investigated 31 patients. Blood samples were taken preoperatively and for 5 days postoperatively. PCT levels were compared with C-reactive protein (CRP), interleukin-6 (IL-6), and blood leucocyte counts (WBC). Results . In uneventful THR PCT levels showed a uniform low-level course with a peak at the second postoperative day. At the fifth day values returned to almost preoperative levels. On contrary, CRP levels remained high during the entire observational period. Only IL-6 levels showed a peak at postoperative day one with a quick and uniform return to preoperative levels. Conclusion . Similar to observations in cardiothoracic, intestinal, and neural surgeries, postoperative course of PCT after primary THR showed a uniform low-level course with a peak at the second postoperative day but below expected levels in systemic infections.